1962
DOI: 10.3133/pp341a
|View full text |Cite
|
Sign up to set email alerts
|

Geology and ore deposits of the Nova Lima and Rio Acima quadrangles, Minas Gerais, Brazil

Abstract: A-1 Introduction 6 2 Location 6 3 Climate, drainage, and topography6 3 Culture and accessibility6 4 Mines and mineral exploration 6 4 Field and laboratory work 6 4 Coordinate system for locations6 5 Acknowledgments6 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
8

Year Published

1973
1973
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 7 publications
1
50
0
8
Order By: Relevance
“…Similar relationships were deduced by Worthington and Kiff (1970), Mangan et al (1984), and Duke and Hodder (1987) for gold deposits in iron-rich exhalites in the central Appalachians. Strong supporting evidence for this concept of exhalative gold came from studies of the Homestake gold deposits by , and subsequently Sawkins and Rye (1974) applied the term Homestake-type deposits to gold ores of this type and suggested that their occurrence was worldwide, and included certain major deposits such as Morro Velho, Brazil (Gair 1962) and the Kolar goldfield, India. Strong supporting evidence for this concept of exhalative gold came from studies of the Homestake gold deposits by , and subsequently Sawkins and Rye (1974) applied the term Homestake-type deposits to gold ores of this type and suggested that their occurrence was worldwide, and included certain major deposits such as Morro Velho, Brazil (Gair 1962) and the Kolar goldfield, India.…”
Section: Gold Ores Of Probable Exhalative Origin: Homestake-type Depomentioning
confidence: 99%
“…Similar relationships were deduced by Worthington and Kiff (1970), Mangan et al (1984), and Duke and Hodder (1987) for gold deposits in iron-rich exhalites in the central Appalachians. Strong supporting evidence for this concept of exhalative gold came from studies of the Homestake gold deposits by , and subsequently Sawkins and Rye (1974) applied the term Homestake-type deposits to gold ores of this type and suggested that their occurrence was worldwide, and included certain major deposits such as Morro Velho, Brazil (Gair 1962) and the Kolar goldfield, India. Strong supporting evidence for this concept of exhalative gold came from studies of the Homestake gold deposits by , and subsequently Sawkins and Rye (1974) applied the term Homestake-type deposits to gold ores of this type and suggested that their occurrence was worldwide, and included certain major deposits such as Morro Velho, Brazil (Gair 1962) and the Kolar goldfield, India.…”
Section: Gold Ores Of Probable Exhalative Origin: Homestake-type Depomentioning
confidence: 99%
“…1). In many cases they have been extensively described (Kitson, 1930;Emmons, 1937;Narayanaswami et al, 1960;Boyle, 1961;Harris, 1961;Gair, 1962;Dorr and Barbosa, 1963;Ferguson, 1968;Slaughter, 1968;Ridler, 1970;Woodall, 1975;Anhaeusser, 1976; Ntiamoah-Agyakwa, 1979; Pye and Roberts, 1981). It is neither the purpose nor within the scope of this paper to review thoroughly their geologic characteristics nor the genetic processes believed to have formed them, which remain controversial.…”
Section: Greenstone-hosted Lode Depositsmentioning
confidence: 95%
“…2400 Ma (Babinski, 1991) or 2100 Ma (Herz, 1970;Teixeira, 1982;Delhal and Demaiffe, 1985;Machado et al, 1989). The mapping of the area by different members of the Dorr team (Guild, 1957;Simmons and Maxwell, 1961;Gair, 1962;Johnson, 1962;Dorr and Barbosa, 1963;Pomerene, 1964;Wallace, 1965;Reeves, 1966;Simmons, 1968a, b;Alves, 1969;Barbosa, 1969;Moore, 1969;O'Rourke, 1969;Herz, 1970Herz, , 1978Maxwell, 1972; A.N. Cunha, B. Ashley, and A.…”
Section: Minas Supergroupmentioning
confidence: 99%